Negotiating normativities: ‘Odin from Lejre’ as challenger of hegemonic orders - Arwill-Nordbladh, Elisabeth (Danish Journal of Archaeology, 2014)
This article focuses on some bodily features of the figurine called ‘Odin from Lejre’. Some corporal characteristics convey an ambivalent touch to the interpretation of the miniature. So, for example, shows the clothing close resemblance to the late Iron Age female dress. This, combined with facial attributes that have been interpreted as a moustache, can be seen as a negotiation of the contemporary hetero-normative gender order. Moreover, the eyes of the figure demonstrate certain irregularities, maybe signifying differences in the visual capacities of the eyes. This corporal exceptionality in relation to (today’s) notions of body-normativity may imply that the Viking Age abled body sometimes was extended to include reduced visual capacity. The processing of both gender-normativity and body-normativity in one and the same precious item, may imply that the high-ranked setting of Lejre included performative practices that were negotiating both heteronormative and body-normative hegemonic orders.